2006
DOI: 10.1016/j.biomaterials.2005.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Polyetheretherketone as a biomaterial for spinal applications

Abstract: Threaded lumbar interbody spinal fusion devices (TIBFD) made from titanium have been reported to be 90% effective for single-level lumbar interbody fusion, although radiographic determination of fusion has been intensely debated in the literature. Using blinded radiographic, biomechanic, histologic, and statistical measures, we evaluated a radiolucent polyetheretherketone (PEEK)-threaded interbody fusion device packed with autograft or rhBMP-2 on an absorbable collagen sponge in 13 sheep at 6 months. Radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
323
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 494 publications
(357 citation statements)
references
References 35 publications
8
323
0
6
Order By: Relevance
“…However, this model can be challenging and studies have produced inconsistent success rates using autograft bone. Ovine single-level interbody fusions utilizing different radiolucent polymers with autograft augmentation, including 70/30 poly (L-lactide-co-D,L-lactide) and PEEK rings, have produced fusion rates of 50 and 71%, respectively [27,28]. Other lumbar interbody fusion cages have also been investigated in sheep, including Bagby and Kuslich (BAK) cages (SpineTech, Minneapolis, MN) which yielded only a 20% rate of fusion at 6 months when supplemented with autograft [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this model can be challenging and studies have produced inconsistent success rates using autograft bone. Ovine single-level interbody fusions utilizing different radiolucent polymers with autograft augmentation, including 70/30 poly (L-lactide-co-D,L-lactide) and PEEK rings, have produced fusion rates of 50 and 71%, respectively [27,28]. Other lumbar interbody fusion cages have also been investigated in sheep, including Bagby and Kuslich (BAK) cages (SpineTech, Minneapolis, MN) which yielded only a 20% rate of fusion at 6 months when supplemented with autograft [35].…”
Section: Discussionmentioning
confidence: 99%
“…A retroperitoneal lateral approach enabled discectomy, distraction of the vertebral bodies, preparation of the endplates, and placement of the interbody device. In order to optimize visualization and provide a more rigorous model for lumbar fusion, PEEK rings were utilized rather than titanium, and instrumentation was not used [27]. The PEEK rings were ''D'' shaped devices, 8 mm thick with a major circumference of 18 mm, 4 mm thick walls, and an internal volume of 0.4 cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Polyetheretherketone (PEEK) is a polymer widely used in orthopaedic and spinal applications such as soft tissue repair and spinal fusion devices as a result of its high strength, fatigue resistance, radiolucency, and favorable biocompatibility in osseous environments [25,38,45,47,50]. However, attributable in part to PEEK's relatively inert and hydrophobic surface, recent evidence has demonstrated that smooth PEEK can exhibit poor osseointegration [9,25] and fibrous capsule formation around the implant [23,34].…”
Section: Introductionmentioning
confidence: 99%
“…It is a high-temperature semi crystalline thermoplastic polymer from the group of polyaryletherketone (PAEK) consisting of an aromatic backbone molecular chain, interconnected by ketone and ether functional groups [5] with the density of 1.3 -1.5 g/cm 3 . Its favorable biocompatible and mechanical properties [5][6], as well as a high melting point (about 343°C), good dimensional stability at high temperatures and chemical stability to nearly all-organic and inorganic chemicals makes it an interesting material for metal-free prosthodontics. One major drawback of PEEK is the greyish and opaque color and the requirement of veneering composites to achieve acceptable esthetics.…”
Section: Introductionmentioning
confidence: 99%